Framework For The Educational Apps Development, Based on Models of Teaching - Cuervo Gómez, William Oswaldo; Ballesteros-Ricaurte, Javier Antonio (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The technological advances made in the mobile communication field over the past few years have all contributed to enhance software and hardware specifications. Initiatives such as those launched by the government of Colombia, which pursues the objective of providing official educational institutions with digital tablets, have motivated the actors in the educational process and the teachers’ interest in proposing strategies for incorporating mobile devices into educational contexts. From this point of view, the present research aims to propose a framework which allows combining technological and pedagogical aspects in the educational apps development process, in order to respond to the needs of the educational environment in which they will be incorporated. This document shows the results of the research carried out in four methodological stages: assessment, conceptualization and characterization, proposal and implementation of the framework, and analysis of results.